Shared decision making: Does a decision aid support patients with an atypical cartilaginous tumor in making a decision about treatment - Petra I. Veldman-Goossen; Claudia Deckers; Edwin F. Dierselhuis; Hendrik W.B. Schreuder; Ingrid C.M. van der Geest (Elsevier, 2022)
Objective: Due to new insights, atypical cartilaginous tumors (ACTs) of the long bones are no longer considered malignant and treatment is shifting from surgery to active surveillance. We developed a decision aid in order to support in shared decision making on treatment.The aim of this study is to evaluate the treatment preferences of patients with an ACT in the long bones. Methods: During thirty-four months, patients received a decision aid digitally with information about the disease, the treatment options, and the risks and benefits of active surveillance and surgical treatment. The given answers to patients' preference questions were evaluated qualitatively in relation to the final choice of treatment. Results: Eighty-four patients were included. None of the patients who preferred active surveillance later underwent surgery. Only four patients underwent surgery based on patient preference. Conclusion: In our experience the decision aid is useful for shared decision making as it provides the patient with information and the clinician with insight into patient's preferences. The preference for treatment generally corresponds to the eventual treatment. Innovation: When treatment changes, due to new insights, a decision aid seems helpful for both patients and clinicians to discuss the treatment that best suits the patient's situation.